Non-family Shareholder Governance and Green Innovation of Family Firms: A Socio-emotional Wealth Theory Perspective - Du, S.; Cao, June (Elsevier, 2023)
We draw on socio-emotional wealth (SEW) theory to investigate the influence of non-family shareholder governance (NFSG) on green innovation in family firms. We find that non-family shareholder holding has no significant impact on green innovation, but the directors appointed by non-family shareholders (NFSDAs) significantly promote the implementation of green innovation strategies in family firms. The underlying mechanisms are characterized by NFSG bringing valuable resources and promoting the firm reputation, which further facilitates green innovation. The effect of NFSG is more pronounced for entrepreneurial family firms and family firms located in high institutional efficiency areas. The green professional backgrounds of NFSDAs and having excess NFSDAs also effectively promote green innovation. Finally, green innovation promotes the long-term orientation of family firms. Through this study, we draw on SEW theory to enrich research on NFSG and green innovation in family firms. Our findings can help family firms achieve a solid basis for long-term orientation.